Repeated sprint ability task dependency: The effect of rugby union specific tasks - Morel, B.; Hautier, C.; Rouffet, D. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The ability of team sport players to repeat maximal efforts, referred as Repeated Sprint Ability (RSA), strongly influences both individual and team performances. It has been shown that RSA is task dependent but it is still mainly studied using cycling or running protocols (Girard and al., 2010). This study proposes to investigate RSA of rugby players during specific rugby tasks as running sprints (RU) but also mauling (MA) and scrummaging (SC) which are repeated all over the game. Methods: 8 rugby players performed three RSA tests interspersed by at least 48h. We used RSA test consisting in 5 repetitions of 5s maximal exertion interspersed with a 20s passive recovery. Three tasks where investigated: RU monitoring average speed, SC using a yoke with a force sensor to measure the average force production over the 5s repetitions and MA assessed with a moving yoke (on wheels) recording the distance of displacement to evaluate the average speed on 5s. To complete the performance data obtained, blood lactate accumulation, EMG recordings of the Vastus Lateralis and Rate of Perceived Exertion (RPE Borg scale) were recorded for each tasks. Results: The repetition of RU, MA and SC induced a decrease in the performance associated of respectively 23%, 13% and 7%. Furthermore, an EMG level decrease was observed only during MA (21%) and SC (13%) while blood lactate accumulation was significant just for RU (9.2 mmol/L) and MA (8.8 mmol/L). Average RPE was higher during the repetition of SC (7.8) compared to MA (7.2) and RU (7.1). Discussion: RSA induced performance decrease for the three tasks tested but the decrease was more important for scrummaging compared to running sprints. Mauling is intermediate as it didn`t differ from both others situations. Furthermore it is interesting to observe that EMG loss is present only for scrummaging and mauling tasks while blood lactate accumulation was significant just for the dynamic tasks. These results are in line with previous studies which demonstrated that voluntary activation failure occurred during the repetition of isometric contractions while the repetition of concentric contraction leads fatigue from peripheral perturbation (Babault and al., 2006). Mauling (slow dynamic task) seems to be intermediate with scrummaging (static) and running sprints (fast dynamic).The three tasks tested on the same RSA test causes different level of fatigue and seem to be linked to different fatigue causes. Thus RSA seems to be task dependent for rugby activity which tends to indicate that specific tests have to be develop and used depending on the players role.